HOW DO HIGH SCHOOL STUDENTS IN MEDAN CITY UNDERSTAND AND IMPLEMENT DIGITAL DETOXIFICATION? - Yovita Sabarina Sitepu; Hendra Harahap; Mickhael Rajagukguk, (INTERNATIONAL JOURNAL OF MODERN TRENDS IN SOCIAL SCIENCES (IJMTSS), 2024)
This study examines the pattern of using digital devices and efforts to implement detoxification among high school students. This study aims to obtain in-depth information on how high school students carry out digital detoxification efforts to reduce the impact of addiction. This type of research is qualitative with a case study method on the senior high school in Medan City, North Sumatra Province. This study uses a focus group discussion approach to obtain information from research informants. The informants comprised 14 students from 6 senior high schools and vocational high schools in Medan City. In this research, students take digital detoxification steps to minimize the negative impact of using digital devices. High school students use digital detoxification to neutralize their addiction to digital media daily. Things to do to detoxify digitally are learning to manage time when using digital devices, limiting internet access, implementing healthy lifestyles such as exercising or socializing, and following a social media detox.